The VANDELS survey: a strong correlation between Ly α equivalent width and stellar metallicity at 3 ≤ z ≤ 5. Issue 1 (9th May 2020) - Cullen, F; McLure, R J; Dunlop, J S; Carnall, A C; McLeod, D J; Shapley, A E; Amorín, R; Bolzonella, M; Castellano, M; Cimatti, A; Cirasuolo, M; Cucciati, O; et al.
ABSTRACT: We present the results of a new study investigating the relationship between observed Ly α equivalent width ( W λ (Ly α)) and the metallicity of the ionizing stellar population (  Z ⋆ ) for a sample of 768 star-forming galaxies at 3 ≤ z ≤ 5 drawn from the VANDELS survey. Dividing our sample into quartiles of rest-frame W λ (Ly α) across the range $-58 \, \rm {\mathring{\rm A}} \lesssim$ W λ (Ly α) $\lesssim 110 \, \rm {\mathring{\rm A}}$, we determine   Z ⋆ from full spectral fitting of composite far-ultraviolet spectra and find a clear anticorrelation between W λ (Ly α) and   Z ⋆ . Our results indicate that   Z ⋆ decreases by a factor ≳ 3 between the lowest W λ (Ly α) quartile (〈 W λ (Ly α)$\rangle =-18\, \rm {\mathring{\rm A}}$ ) and the highest W λ (Ly α) quartile (〈 W λ (Ly α)$\rangle =24\, \rm {\mathring{\rm A}}$ ). Similarly, galaxies typically defined as Lyman alpha emitters (LAEs; W λ (Ly α) $\gt 20\, \rm {\mathring{\rm A}}$ ) are, on average, metal poor with respect to the non-LAE galaxy population ( W λ (Ly α) $\le 20\, \rm {\mathring{\rm A}}$ ) with   Z ⋆ non-LAE ≳ 2 ×   Z ⋆ LAE . Finally, based on the best-fitting stellar models, we estimate that the increasing strength of the stellar ionizing spectrum towards lower   Z ⋆ is responsible for ${\simeq}15{-}25{{\ \rm per\ cent}}$ of the observed variation in W λ (Ly α) across our sample, with the remaining contribution (${\simeq}75{-}85{{\ \rm per\ cent}}$ ) being due to a decrease in the H i /dust covering fractions in low-  Z ⋆ galaxies.